ANALYSIS OF THE FIXED-ASSET ACCOUNTING IMPLEMENTATION IN THE REGIONAL FINANCIAL AND REVENUE MANAGEMENT AGENCY OF PAMEKASAN - Qomariyah, Nur Lailatul; Amar, Siti Salama (Jurnal Ekonomi Pembangunan, 2023)
This research examines the Government Accounting Standards Statement (PSAP) No.07 which is applied to the Regional Financial and Revenue Management Agency of Pamekasan Regency regarding Fixed Assets. The aim is to find out how Fixed Asset accounting in accordance with PSAP No.07 based on Government Regulation No.71 of 2010 is applied and compared in BPKPD Pamekasan Regency. The research was conducted in a qualitative descriptive manner. Interviews, observations and documentation were used to collect data. The results of the research show that BPKPD Pamekasan Regency has complied with and fulfilled the requirements for managing Fixed Assets, in terms of classification, recognition, measurement, depreciation, retirement and disposal, and disclosure. BPKPD Pamekasan Regency has also fulfilled the provisions of PSAP No.07 stipulated by PP No.71 of 2010.